SOSIALISASI IMPLEMENTASI PROGRAM PERILAKU HIDUP BERSIH DAN SEHAT BAGI PEKERJA MIGRAN INDONESIA DI JOHOR BAHRU, MALAYSIA - Syamsi Setiadi; Yasep Setiakarnawijaya; Puti Zulharby; Siti Masyitoh (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2024)
Abstract Indonesian Migrant Workers (IMW) in the Johor Bahru region of Malaysia as community service partners, face problems related to the quality of personal and environmental health due to workplace conditions, limited health facilities and infrastructure, lack of knowledge, understanding, insight and awareness of Indonesian migrant workers to want to practice cleanliness and healthy living behavior. This health quality problem has an impact on the quality of life of migrant workers in Johor Bahru, Malaysia. In order and in an effort to increase the knowledge, insight and awareness of Indonesian migrant workers in the Johor Bahru region towards a clean and healthy quality of life which includes self, family, community and the environment, this community service activity is carried out in collaboration with LPPM-ALPTKNI and collaborating with one of the universities in Johor, namely Universiti Tun Hussein Onn Malaysia (UTHM). This activity will also support the efforts of the Indonesian Community Center (ICC) by the Indonesian Consulate General in Johor Bahru to empower Indonesian migrant workers in Malaysia. The approach to partners was carried out using an institutional approach to obtain accurate data about IMW conditions at the location. Partner participation is carried out with the Clean and Healthy Living Behavior (PHBS) program which is implemented within 1-2 days. The methods used in training are seminars/workshops and mentoring. This service activity aims to: 1) increase knowledge, understanding, insight and awareness of IMW to want to adopt clean and healthy living behavior; 2) increase understanding of behavior and awareness of the importance of maintaining a healthy environment for a better quality of life. Abstrak Pekerja Migran Indonesia (IMW) di wilayah Johor Bahru Malaysia sebagai mitra pengabdian masyarakat, menghadapi permasalahan terkait kualitas kesehatan diri dan lingkungan akibat kondisi tempat kerja, sarana dan prasarana kesehatan yang terbatas, kurangnya pengetahuan, pemahaman, wawasan, dan kesadaran pekerja migran Indonesia untuk ingin melakukan kebersihan dan sehat perilaku hidup. Masalah kualitas kesehatan ini berdampak pada kualitas hidup pekerja migran di Johor Bahru, Malaysia. Dalam rangka dan upaya meningkatkan pengetahuan, wawasan, dan kesadaran para pekerja migran Indonesia di wilayah Johor Bahru terhadap kualitas hidup yang bersih dan sehat yang meliputi diri sendiri, keluarga, masyarakat, dan lingkungan, kegiatan pengabdian masyarakat ini dilaksanakan bekerja sama dengan LPPM-ALPTKNI dan bekerja sama dengan salah satu perguruan tinggi di Johor, yaitu Universiti Tun Hussein Onn Malaysia (UTHM). Kegiatan ini juga akan mendukung upaya Indonesian Community Center (ICC) oleh KJRI Johor Bahru dalam rangka pemberdayaan pekerja migran Indonesia di Malaysia. Pendekatan kepada mitra dilakukan dengan pendekatan kelembagaan untuk mendapatkan data yang akurat tentang kondisi IMW di lokasi. Partisipasi mitra dilakukan dengan program Perilaku Hidup Bersih dan Sehat (PHBS) yang dilaksanakan dalam waktu 1-2 hari. Metode yang digunakan dalam pelatihan adalah seminar/workshop dan pendampingan. Kegiatan pengabdian ini bertujuan untuk: 1) meningkatkan pengetahuan, pemahaman, wawasan, dan kesadaran IMW untuk ingin melakukan perilaku hidup bersih dan sehat; 2) meningkatkan pemahaman perilaku dan kesadaran akan pentingnya menjaga lingkungan yang sehat demi kualitas hidup yang lebih baik.